Perinatal Outcome Following Assisted Reproductive Technology in a Tertiary Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Objective:  Pregnancies following assisted reproductive technologies have become much more common in tertiary hospitals with  neonatal  intensive  care  facilities.  The  aim  of  this  study  is  to  compare  the  perinatal  outcome  of  women  who  conceived  through  Assisted  Reproductive  Technologies  with  who  conceived  naturally. Method:  This  retrospective  cohort  study  was  conducted  in  BIRDEM  Women  and  Children  Hospital  from  1st  March  2023  to  31st  March  2024.  The  study  population  was  divided  into  two  groups.  Group  1  was  the  ART  pregnancy  (In  Vitro  Fertilization,  IVF)  group  and  Group  2  was  the  naturally  conceived  group.  The  perinatal  outcome  of  two  groups  of  women  admitted  in  the  hospital  during  that  period  of  time  for  delivery  was  compared. Result:  Mean maternal  age  of  ART  pregnancy  was  33.89+4.86  years,  and  29.26+5.32  years  in natural  pregnancy.  Women  with  ART  pregnancy  in  comparison to  natural  pregnancy  had statistically  significant  advanced  maternal  age  (>  35yr)  (45/110  Vs  26/130;  p=0.001);  multiple pregnancy  (63.6%  Vs